Entrevista a Nelson Manrique - Drinot, Paulo (2023)
In this interview, conducted in June 2023, historians Paulo Drinot and Nelson Manrique discuss the latter’s biography, historiographical production, political activism, university teaching and journalistic work. The interview opens a window on the life and work of one of the most important and influential intellectuals in Peru in the second half of the twentieth century and the beginning of the twenty-first century.